2009
DOI: 10.1007/s00330-009-1698-6
|View full text |Cite
|
Sign up to set email alerts
|

Are there any differences in acute adverse reactions among five low-osmolar non-ionic iodinated contrast media?

Abstract: The incidence of acute adverse reactions may be reduced in younger patients by using iopamidol, iohexol and ioversol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 13 publications
(21 reference statements)
5
31
2
Order By: Relevance
“…Sutton et al also reported that visipaque is well tolerated in the early phase of injection (6). In a study by Gomi et al, immediate reaction was reported in 2.7 % in iodixanol in comparison with 3.5 % in iopromide (7). Skin reaction is mostly mild skin reaction which will be resolved simply.…”
Section: Discussionmentioning
confidence: 98%
“…Sutton et al also reported that visipaque is well tolerated in the early phase of injection (6). In a study by Gomi et al, immediate reaction was reported in 2.7 % in iodixanol in comparison with 3.5 % in iopromide (7). Skin reaction is mostly mild skin reaction which will be resolved simply.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Gomi, et al conducted a prospective study in a large population, unlike previous studies. They reported that iopromide had a higher incidence of adverse reactions compared to other RCM products (including iopamidol, iohexol, and ioversol) . Additionally, Seong et al evaluated 6624 adverse reactions to low‐osmolar RCMs.…”
Section: Discussionmentioning
confidence: 99%
“…Although LOCM have very similar molecular structures, the individual media have different safety profiles. Gomi et al (22) found that the proportion of patients experiencing AE varied by LOCM (iomeprol, 3.9%; iopamidol, 2.2%; iohexol, 2.0%; iopromide, 3.5%; ioversol, 1.8%; and all five combined, 2.7%) among the 8,931 patients who underwent contrast-enhanced CT. However, to our knowledge, this is the first study specifically designed to compare the frequency of AEs of iodinated contrast media by organ class between individual media, as well as between low-osmolar and iso-osmolar media.…”
Section: Discussionmentioning
confidence: 99%